Bioplastics from Avocado Seed Starch : Effects of Chitosan and PVA on Mechanical Properties, Water Resistance, and Biodegradability - Wahyudi, Mohamad Nur; Hartanti, Adelia; Sari, Dessy Agustina; Hakim, Muhammad Fahmi; Aeni, Alfieta Rohmaful (Fakultas Teknologi Industri - Universitas Muslim Indonesia, 2025)
A sustainable alternative to traditional petroleum-based plastics, bioplastics produced from avocado seed starch can help alleviate some of the environmental challenges presented by plastic waste. However, these products still need to improve their mechanical properties and water resistance for industrial use. The purpose of this study is to find out how changes in the amounts of chitosan and polyvinyl alcohol (PVA) affect the mechanical strength, water resistance, and biodegradability of bioplastics made from avocado seed starch. The solution-casting method prepared starch-based bioplastics using chitosan (2.5–4.5 g), PVA (2.5–5%) as filler, and glycerol as a plasticizer. This study found that adding more chitosan increased the tensile strength, reaching a maximum value of 30.696±0.106 N/mm2 in the SNI 7188.7:2016, which was higher than the tensile strength value of the N3 sample. The samples N1 and M1 demonstrated the highest elongation at break of 35.700±4.776% and the lowest water uptake of 5.167%, indicating a 94.833% water resistance. The plastics underwent complete biodegradation under soil conditions after 60 days. This led to valuable results, confirming that avocado seed starch-based bioplastics, as engineering materials for food packaging, have enormous potential for application in the industry. This research needs to increase the water resistance or scale it up for industrial production